2014
DOI: 10.1017/s000711451400227x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of oats and the impact of processing operations on nutrition and health benefits

Abstract: Oats are a uniquely nutritious food as they contain an excellent lipid profile and high amounts of soluble fibre. However, an oat kernel is largely non-digestible and thus must be utilised in milled form to reap its nutritional benefits. Milling is made up of numerous steps, the most important being dehulling to expose the digestible groat, heat processing to inactivate enzymes that cause rancidity, and cutting, rolling or grinding to convert the groat into a product that can be used directly in oatmeal or can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 21 publications
3
111
0
10
Order By: Relevance
“…The ones used in the research study were morphologically comparable to whole-oat flakes (0.51-0.76 mm) (Decker et al 2014) which were confirmed by microphotography (Fig. 2).…”
Section: Morphology Of Raw Materialssupporting
confidence: 70%
See 1 more Smart Citation
“…The ones used in the research study were morphologically comparable to whole-oat flakes (0.51-0.76 mm) (Decker et al 2014) which were confirmed by microphotography (Fig. 2).…”
Section: Morphology Of Raw Materialssupporting
confidence: 70%
“…The further statistical calculation of a difference between all three processing conditions vs. the gelatinization temperature revealed that the solids release was the highest for typical cooking while the content of non-hydrolyzed starch was the highest in MW irradiated samples especially in shorter treatment (MW3). The oat flakes have initial higher starch content due both the morphological form and processing method (Decker et al 2014). The overall starch content of oat bran is also high because of residual fat and protein presence in aleuronic layer in oat grain which makes full separation of endosperm impossible.…”
Section: The Morphological Change and Carbohydrate Release During Micmentioning
confidence: 99%
“…We can also note that different processing techniques on oats such as malting and roasting can help in keeping their high nutritive value and their resulting weaning mixes; it is also found that both oat roasted and malted weaning gruels are accepted by the panel members of sensory quality evaluation 26 . Thus, child malnutrition, caused by the introduction of traditional weaning foods, would be improved by simple processing techniques on cereals such as oats whose formulated weaning mix is being increased in nutritional value 26,27 .…”
Section: Nutritional Value Of Oat (Avena Sativa L)mentioning
confidence: 99%
“…[3] Oats are rich in phenolic compounds, protein, dietary fibre, unsaturated fatty acids, and starch (~60%). [4,5] In comparison to wheat, oat grains have 2-5 times more lipids and are rich in hydrolytic enzymes. [6] Starch is the most abundant storage reserve carbohydrate in plants.…”
Section: Introductionmentioning
confidence: 99%